Análisis jurídico y doctrinario de la emancipación judicial, causas y efectos que genera esta figura jurídica en el emancipado - Torres Jimenez, Alex Paul (2024)
This study aims to address judicial emancipation in the legal field to determine its causes and effects on the emancipated individual. To achieve this, I intend to analyze local regulations such as the Constitution of Ecuador, the Organic Code for Children and Adolescents, the Civil Code, and the Labor Code. In these legal frameworks, I will determine the scope of emancipation and the legal institutions related to this concept, including the family and parental authority. The subjects involved in this process are children, adolescents, and young adults. The legal effects of emancipation impact parents, family members of minors, and legal custodians. To meet these objectives, I plan to adopt a qualitative approach, including surveys and interviews with scholars and legal professionals specializing in family, childhood, and adolescent law. On a doctrinal level, I aim to deepen the study of the institutions involved in judicial emancipation, drawing on the insights of internationally recognized legal experts in this field. In the realm of comparative law, I will analyze the legislation of three countries: Colombia, Chile, and Spain, to identify similarities and differences between judicial emancipation in Ecuador and these states. From a sociological perspective, I will examine the views expressed by the interviewed judges in the family, childhood, and adolescence unit in the city of Loja. This will allow me to identify the customs and traditions in our society that lead minors to pursue judicial emancipation.